Designing a Haptic Boot for Space With Prompt Engineering: Process, Insights, and Implications - Mohammad Amin Kuhail; Jose Berengueres; Fatma Taher; Sana Zeb Khan; Ansah Siddiqui (IEEE Access)
Recent literature indicates the potential of applying Artificial Intelligence (AI) tools to enhance ideation outcomes and optimize functionality across various engineering disciplines. However, a comprehensive understanding of applying AI in the design process is lacking, particularly regarding projects involving innovative design. Here, we address the integration of AI in a case study project. The project goal is to design a haptic boot to be used on Mars. We apply a popular AI tool, ChatGPT-3.5, to each design step, from the requirement gathering phase to the prototyping and testing phase. To assess the merit of the AI contributions, we asked eight domain experts to give qualitative feedback. The results indicate that current AI tools can provide a valuable starting point in the requirements and design phases. However, we noted instances of hallucinations and poor traceability. Finally, the experts’ evaluation points out that the AI-proposed requirements and design are missing key elements expected as an outcome in an engineering design process. This study offers insight into the practical application of AI through a specific engineering design process.